Age-Related Changes in Electrophysiological and Neuropsychological Indices of Working Memory, Attention Control, and Cognitive Flexibility - Peltz, Carrie B.; Gratton, Gabriele; Fabiani, Monica (Frontiers in Psychology, 2011)
Older adults exhibit great variability in their cognitive abilities, with some maintaining high levels of performance on executive control tasks and others showing significant deficits. Previous event-related potential (ERP) work has shown that some of these performance differences are correlated with persistence of the novelty/frontal P3 in older adults elicited by task-relevant events, presumably reflecting variability in the capacity to suppress orienting to unexpected but no longer novel events. In recent ERP work in young adults, we showed that the operation-span task (OSPAN, a measure of attention control) is predictive of the ability of individuals to keep track of stimulus sequencing and to maintain running mental representations of task stimuli, as indexed by the parietally-distributed P300 (or P3b). Both of these phenomena reflect aspects of frontal function (cognitive flexibility and attention control, respectively). To investigate these phenomena we sorted both younger and older adults into low- and high-working memory spans and low- and high-cognitive flexibility subgroups, and examined ERPs during an equal-probability choice reaction-time task. For both age groups (a) participants with high OSPAN scores were better able to keep track of stimulus sequencing, as indicated by their smaller P3b to sequential changes; and (b) participants with lower cognitive flexibility had larger P3a than their high-scoring counterparts. However, these two phenomena did not interact suggesting that they manifest dissociable control mechanisms. Further, the fact that both effects are already visible in younger adults suggests that at least some of the brain mechanisms underlying individual differences in cognitive aging may already operate early in life.